Accessibility of academic libraries for students living with disabilities in selected South African Universities - Du Toit, Sarah (Library and Information Studies Centre (LISC), 2025)
Grounded in the social model of disability (Oliver, 1990), this study assessed the accessibility of academic libraries for students living with disabilities (SWDs) in selected South African universities. Academic libraries are central to higher education, yet systemic, physical and technological barriers often hinder access for students with mobility and visual impairments. The study investigated how academic libraries facilitate accessibility and inclusion for these students by evaluating their ability to engage with library services without assistance. The research adopted a qualitative multiple case study design, focusing on two South African universities: the University of Cape Town and the University of the Western Cape. Data were collected through semi-structured interviews with eighteen participants, comprising four library staff members and fourteen SWDs, alongside non-participant observation and document analysis. Non-participant observation was conducted in various library spaces to examine the accessibility of building entrances, service desks, computer workstations, signage, shelving arrangements and the availability and use of assistive technologies. The analysed documents included UCT's Disability Policy (2021), Transformation Report (2023), and Disability Policy Council Report (2022), as well as UWC's Policy on Students with Disability (2007) and Library Annual Report (2021). The study was guided by the following key objectives: to examine the accessibility measures currently implemented in academic libraries, evaluate existing policies supporting physically and visually impaired students, identify physical and non-physical barriers to access and assess the role of library staff and assistive technologies in creating inclusive learning environments. Findings revealed that while various accessibility measures and assistive technologies are available, gaps remain in the areas of infrastructure, staff training and institutional policy implementation. Contributing factors included financial constraints, limited awareness and inconsistent institutional commitment. The study recommended the development of formal accessibility policies, dedicated funding for accessibility initiatives, targeted training programmes for library staff and structured feedback mechanisms to strengthen inclusive service delivery. This research contributes to the discourse on disability inclusion in higher education and offers recommendations for improving academic library services for SWDs in South Africa.